Evaluation of Challawa Tannery Wastewater as Mixing and Curing Water for Concrete Production - IDRIS, Ahmad (FUDMA Journal of Engineering and Technology, 2026)
The increasing scarcity of freshwater resources and the growing environmental challenges associated with industrial wastewater disposal have made it necessary to explore alternative water sources for concrete production. The study was carried out to assess the suitability of tannery wastewater in Challawa Industrial Estate, Kano State, Nigeria as mixing and curing water for concrete. Concrete specimens were prepared in three different mix conditions: concrete mixed and cured with fresh water (control), concrete mixed with tannery wastewater and cured with fresh water and concrete mixed and cured with tannery wastewater. Laboratory investigations included chemical characterization of the wastewater and compressive strength testing of concrete cubes at 3, 7, and 28 days. Results showed that the wastewater possessed a pH of 9.23, chloride concentration of 5.2 mg/L, total suspended solids of 2.68 mg/L, turbidity of 0.9 NTU, and settleable solids of 34 mL/L. The compressive strengths at 28 days were 27.1 MPa, 18.7 MPa, and 26.6 MPa for the control, wastewater-freshwater, and wastewater-wastewater mixes respectively. The results indicate that although tannery wastewater may adversely affect early-age strength development, concrete mixed and cured in wastewater achieved compressive strengths comparable to conventional concrete after 28 days. The results suggest that the tested tannery wastewater has potential for use as mixing and curing water for concrete under controlled laboratory conditions, subject to compliance with applicable water-quality requirements and further durability assessment.